Analysis the Causal Relationship between Oil Exports and Economic Growth in Iraq - علي, ازهار حسن (Journal of Economics and Administrative Sciences, 2017)
The oil exports play a vital role in supporting economic development and raise the economic growth. The oil exports can increase the economic growth via three main channels which are supporting the productive, distributive and service sectors; increasing the investment and capital formation; and increasing the employment rate.However, the oil exports did not have an important role in increasing the economic growth in Iraq. Therefore, it also did not provide the required support to other economic sectors, neither participated in increase the employees’ skills nor increase the investment rate. It may slightly contribute in enhancement the infrastructure that can attract the public and private investments. In the meantime, it did not contribute in improve the employment. The paper finds that there is no causal relationship between the growth rate of oil exports and the rate of economic growth by using Granger causality test. This can be interpreted that the Iraqi economy is single side economy. In other words, the increase in the oil exports did not contribute in increase the investments in the other economic sectors by importing the capital goods necessary for investment. This is clearly revealed through raise the proportion of oil sector in GDP and fall the proportion of other economic sectors in GDP.